Motion analysis of the cervical spine during extension and flexion: Reliability of the vertebral marking procedure. (November 2018) - Plocharski, Maciej; Lindstroem, Rene; Lindstroem, Cassandra Frydendal; Østergaard, Lasse Riis
Highlights: A cervical joint motion analysis with no experience in radiographic image analysis. We develop a method for marking the occiput and for assessment of the C0-to-C7 motion. Fluoroscopic image marking was performed by experienced and inexperienced researchers. We report the average motion marking error of − 0 . 12 ∘ across examiners and images. The procedure demonstrates lower marking errors compared to other published studies. Abstract: Cervical spine motion analysis using videofluoroscopy is currently a technique without a gold standard. We demonstrate the reliability of a rigid and reliable analysis methodology for cervical motion using videofluoroscopic images, representing the entire range of motion during flexion and extension, from the neutral position to the end-range in the sagittal plane. Two researchers with radiography and vertebral marking expertise, and two inexperienced researchers with 10 hours of training manually marked anatomical structures on fluoroscopic images in a procedure designed to control for vertebral rotation around the mid-plane axis. The average marking error across examiners and images was − 0 . 12 ∘ (standard deviation: 0.88°), and the intraexaminer error ranged from − 1 . 00 ∘ to 1.61° (standard deviation range: 0.27°–1.19°). Our method demonstrated lower errors compared to the higher resolution X-ray studies, and proved that vertebral marking can be performed by persons with no experience in radiographic image analysis.